Modulation of Gut Microbiota in Rats by Hydrolyzed-Glucomannan from Amorphophallus oncophyllus - Satiti, Rani; Utami, Tyas; Widada, Jaka; Harmayani, Eni (Trends in Sciences, 2025)
Gut microbiota plays a crucial role in maintaining host health, with dietary fibers being key modulators. This study evaluates the effects of porang glucomannan hydrolysate (PH), a novel prebiotic, on gut microbiota and short-chain fatty acid (SCFA) production in rats. For 21 days, rats were fed diets containing cellulose (CF), a fiber-free diet (NF), porang glucomannan (PG), PH, or inulin (IN). Gut microbiota composition was assessed using Ribosomal Intergenic Spacer Analysis (RISA) and 16S rRNA sequencing, while SCFA levels were measured via gas chromatography. The findings revealed differences in gut microbiota composition at the phylum level: the CF, NF, and PG groups were predominantly composed of Bacteroidota, Firmicutes, and Proteobacteria, whereas the PH and IN groups were mainly dominated by Firmicutes, Bacteroidota, and Actinobacteriota. Notably, at the genus level, SCFA-producing bacterial groups, such as Lactobacillus, Allobaculum, Bifidobacterium, and Blautia, were identified only in the PH and IN groups. This was further corroborated by the higher SCFA concentrations found in the PH and IN groups compared to the other treatment groups. These findings suggest that the inclusion of PH in rats’ diets positively affects the modulation of gut microbiota and increases SCFA concentrations in the cecum, showing effects similar to those of inulin, a commercial prebiotic. Consequently, PH holds the potential as a functional food that supports gastrointestinal health. HIGHLIGHTS The hydrolysis process of porang glucomannan (PG) significantly altered the composition of gut microbiota in rats. Ribosomal Intergenic Spacer Analysis (RISA) and beta diversity measurements indicated that the group receiving PG formed a distinct cluster compared to the group given porang glucomannan hydrolysate (PH). The gut microbiota in the PH group closely resembled that of rats fed with inulin (IN). The PH group had a greater abundance of short-chain fatty acid (SCFA)-producing bacteria, including Lactobacillus, Allobaculum, Bifidobacterium, and Blautia, which were absent in the PG group. Consequently, SCFA levels were significantly higher in the PH group than in the PG group. GRAPHICAL ABSTRACT